In Vivo Imaging of the Segregation of the 2 Chromosomes and the Cell Division Proteins of Rhodobacter sphaeroides Reveals an Unexpected Role for MipZ - Nelly Dubarry (American Society for Microbiology, 2019)
ABSTRACT Coordinating chromosome duplication and segregation with cell division is clearly critical for bacterial species with one chromosome. The precise choreography required is even more complex in species with more than one chromosome. The alpha subgroup of bacteria contains not only one of the best-studied bacterial species, Caulobacter crescentus, but also several species with more than one chromosome. Rhodobacter sphaeroides is an alphaproteobacterium with two chromosomes, but, unlike C. crescentus, it divides symmetrically rather than buds and lacks the complex CtrA-dependent control mechanism. By examining the Ori and Ter regions of both chromosomes and associated ParA and ParB proteins relative to cell division proteins FtsZ and MipZ, we have identified a different pattern of chromosome segregation and cell division. The pattern of chromosome duplication and segregation resembles that of Vibrio cholerae, not that of Agrobacterium tumefaciens, with duplication of the origin and terminus regions of chromosome 2 controlled by chromosome 1. Key proteins are localized to different sites compared to C. crescentus. OriC1 and ParB1 are localized to the old pole, while MipZ and FtsZ localize to the new pole. Movement of ParB1 to the new pole following chromosome duplication releases FtsZ, which forms a ring at midcell, but, unlike reports for other species, MipZ monomers do not form a gradient but oscillate between poles, with the nucleotide-bound monomer and the dimer localizing to midcell. MipZ dimers form a single ring (with a smaller diameter) close to the FtsZ ring at midcell and constrict with the FtsZ ring. Overproduction of the dimer form results in filamentation, suggesting that MipZ dimers are regulating FtsZ activity and thus septation. This is an unexpected role for MipZ and provides a new model for the integration of chromosome segregation and cell division. IMPORTANCE Cell division has to be coordinated with chromosome segregation to ensure the stable inheritance of genetic information. We investigated this coordination in the multichromosome bacterium Rhodobacter sphaeroides. By examining the origin and terminus regions of the two chromosomes, the ParA-like ATPase MipZ and FtsZ, we showed that chromosome 1 appears to be the “master” chromosome connecting DNA segregation and cell division, with MipZ being critical for coordination. MipZ shows an unexpected localization pattern, with MipZ monomers interacting with ParB of the chromosome 1 at the cell poles whereas MipZ dimers colocalize with FtsZ at midcell during constriction, both forming dynamic rings. These data suggest that MipZ has roles in R. sphaeroides in both controlling septation and coordinating chromosome segregation with cell division.